Perspective Planning and Policy for Commercial Energy Part I Demand for Commercial Energy, Longrun Availability of Energy Resources and Perspective Planning for Hydrocarbon and Electrical Energy Volume III - Planning Commission (Planning Commission, 1988)
This report provides a comprehensive analysis of India's commercial energy demand, emphasizing long-term projections for hydrocarbon and electrical energy through integrated modeling. Key findings include projected energy requirements up to 2004-05 based on GDP growth rates of 5.5%, 6%, and 7%. It highlights that the total consumption of electricity for 2004-05 could reach approximately 1,165 billion kWh, with a significant dependency on coal and gas for power generation. The study further underscores the need for strategic capacity planning, emphasizing coal as a primary energy resource and exploring the regional distribution of necessary coal reserves. Additionally, it presents cost considerations for oil and natural gas, proposing optimal allocation of resources for meeting both industrial and agricultural energy needs, while suggesting that complementary roles of coal and gas are critical in the evolving energy landscape.
Assisted By The Energy Modelling Team
Assisted By The Energy Modelling Team
Keywords: Demand Projections; Energy Resource Availability; Investment Needs; Policy Implications; Installed Capacity Needs; Generation Requirements; Capacity Composition; Investment Projections; Regional Disparities